2010
DOI: 10.4103/1596-3519.68364
|View full text |Cite
|
Sign up to set email alerts
|

Contact tracing / pre-employment screening for pulmonary tuberculosis: Should positive mantoux test necessitates routine chest X-ray?

Abstract: It is concluded that other ancillary tests like sputum examination and/or, where available, Interferon and ESAT tests should be carried out before chest radiograph is requested in subjects with positive Mantoux reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 8 publications
1
5
0
1
Order By: Relevance
“…Although the radiation dose one is exposed to during a chest radiograph is fairly low (0.02 mSv) [3], this is unnecessary radiation for the large majority of individuals given low rate of diagnostic yield. Our findings are in line those of other studies which have also shown the low rate of diagnostic yield of routine chest radiography in mass routine chest x-ray [13,14] even in patients with positive purified protein derivative tests [15]. Considering the large numbers of prospective subjected to chest rays throughout the country, it would add significantly to the collective radiation dose of a given population.…”
Section: Discussionsupporting
confidence: 90%
“…Although the radiation dose one is exposed to during a chest radiograph is fairly low (0.02 mSv) [3], this is unnecessary radiation for the large majority of individuals given low rate of diagnostic yield. Our findings are in line those of other studies which have also shown the low rate of diagnostic yield of routine chest radiography in mass routine chest x-ray [13,14] even in patients with positive purified protein derivative tests [15]. Considering the large numbers of prospective subjected to chest rays throughout the country, it would add significantly to the collective radiation dose of a given population.…”
Section: Discussionsupporting
confidence: 90%
“…TST has been widely used as a screening test in many countries and has contributed substantially to generate valuable epidemiological information on infection trends and on the magnitude of the disease (Harstad et al, 2009;Parenti et al, 1987). Moreover, TST is a valuable tool for the screening of household contacts and suspected cases of TB in BCG vaccinated subjects and in population with high BCG vaccination coverage (Adeyekun et al, 2010).…”
Section: Immunological Test Tuberculin Skin Test (Tst)mentioning
confidence: 99%
“…Lain halnya dengan penelitian yang dilakukan di Nigeria dimana tidak ada hubungan yang signifikan antara hasil uji tuberkulin dengan gambaran foto toraks (p=0,106). 6 Tabel 6. Hubungan gambaran foto toraks dan uji tuberkulin Jika dilihat hubungan setiap gambaran foto toraks dengan uji tuberkulin, didapatkan hubungan negatif sedang antara uji tuberkulin dan pembesaran kelenjar dan pelebaran hilus (p=0,046).…”
Section: Hubungan Gambaran Foto Toraks Dan Uji Tuberkulinunclassified